Assessment of Alveolar Macrophage Dysfunction Using an in vitro Model of Acute Respiratory Distress Syndrome - Mahida, Rahul Y.; Scott, Aaron; Parekh, Dhruv; Lugg, Sebastian T.; Belchamber, Kylie B. R.; Hardy, Rowan S.; Matthay, Michael A.; Naidu, Babu; Thickett, David R. (Frontiers in Medicine, 2021)
Background: Impaired alveolar macrophage (AM) efferocytosis may contribute to acute respiratory distress syndrome (ARDS) pathogenesis; however, studies are limited by the difficulty in obtaining primary AMs from patients with ARDS. Our objective was to determine whether an in vitro model of ARDS can recapitulate the same AM functional defect observed in vivo and be used to further investigate pathophysiological mechanisms. Methods: AMs were isolated from the lung tissue of patients undergoing lobectomy and then treated with pooled bronchoalveolar lavage (BAL) fluid previously collected from patients with ARDS. AM phenotype and effector functions (efferocytosis and phagocytosis) were assessed by flow cytometry. Rac1 gene expression was assessed using quantitative real-time PCR. Results: ARDS BAL treatment of AMs decreased efferocytosis (p = 0.0006) and Rac1 gene expression (p = 0.016); however, bacterial phagocytosis was preserved. Expression of AM efferocytosis receptors MerTK (p = 0.015) and CD206 (p = 0.006) increased, whereas expression of the antiefferocytosis receptor SIRPα decreased following ARDS BAL treatment (p = 0.036). Rho-associated kinase (ROCK) inhibition partially restored AM efferocytosis in an in vitro model of ARDS (p = 0.009). Conclusions: Treatment of lung resection tissue AMs with ARDS BAL fluid induces impairment in efferocytosis similar to that observed in patients with ARDS. However, AM phagocytosis is preserved following ARDS BAL treatment. This specific impairment in AM efferocytosis can be partially restored by inhibition of ROCK. This in vitro model of ARDS is a useful tool to investigate the mechanisms by which the inflammatory alveolar microenvironment of ARDS induces AM dysfunction.